2022
DOI: 10.3390/sym14071408
|View full text |Cite
|
Sign up to set email alerts
|

Hopf Bifurcation and Control of a Fractional-Order Delay Stage Structure Prey-Predator Model with Two Fear Effects and Prey Refuge

Abstract: A generalized delay stage structure prey-predator model with fear effect and prey refuge is considered in this paper via introducing fractional-order and fear effect induced by immature predators. Hopf bifurcation and control of this system are investigated though regarding the delay as the parameter. Firstly, by using the method of linearization and Laplace transform, the roots of the characteristic equation of the linearized system of the original system are discussed, and the sufficient conditions for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Given the practical implications of ecosystems, we focus on the coexisting equilibrium. If 1 + aβ − β > 0, then there is unique positive equilibrium E * (ρ * , θ * ) of system (6), where…”
Section: Tipping Dynamics Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Given the practical implications of ecosystems, we focus on the coexisting equilibrium. If 1 + aβ − β > 0, then there is unique positive equilibrium E * (ρ * , θ * ) of system (6), where…”
Section: Tipping Dynamics Analysismentioning
confidence: 99%
“…(i) If (H4) and (H8) are satisfed, then the trajectories of system (6) converge to the equilibrium point E * for all τ ≥ 0. (ii) If either (H5) or (H6), (H7), and (H8) are satisfed, the trajectories of system (6) tend to E * for τ < τ 0 and is far from E * for τ > τ 0 . System (iii) A Hopf bifurcation is produced at E * when τ � τ 0 and a periodic Oscillation appears.…”
Section: Tipping Induced By Hopfmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [3], Cresswell [4], Xu [5] showed that the fear that consider by the predator is greater effect on the prey species than the direct killing. Lan et al [6] interpreted that the fear effect may occur from not only adult predators but also from juvenile one. Fractional derivatives and integrals have provided a better tool to understanding some biological models, especially differential equations models have been interested due to the memory effect which exists in most biological systems [7,8].…”
Section: Introductionmentioning
confidence: 99%